Analysis of Generation Z Financial Behavior in the Era of Cashless Society - Siregar, Elita; Astuti, Ratna Fitri; Ellyawati, Noor Ellyawati, (Journal of Economics Education and Entrepreneurship, 2025)
This study aims to determine how the financial behavior of students in the era of cashless society. The study used a survey type of research, with a descriptive quantitative approach. The number of samples used was 138 students, the data was obtained by distributing questionnaires. Data analysis used in the study is descriptive data and percentage calculations. Based on the results of the study, it shows that students have good financial behavior in managing their finances by comparing prices between stores or supermarkets before deciding on a purchase to be the most dominant indicator felt by students. Students of the Economics Education Study Program have financial behavior that tends to be good in making a budget for expenses and spending, recording daily expenses and spending and comparing prices between stores before deciding on a purchase. Students realize that finances need to be planned properly because financial planning and management are very important for future life.